Demographics of Tenure-Stream Music Faculty in Canadian Post-secondary Institutions - Bergonzi, Louis; Yerichuk, Deanna; Galway, Kiera; Gould, Elizabeth (Intersections, 2015)
This study provides a snapshot of tenure at Canadian post-secondary music institutions, with a particular focus on gender and race/ethnicity. The data show tenure has been granted at high rates over a five-year period, and that women are no more or less likely to achieve tenure than men. However, more men than women hold both tenured and tenure-track positions, at a ratio of 2:1. The sample size of non-white faculty was not large enough to conduct statistical analyses about tenure rates in relation to race/ethnicity, although the extremely low rates of non-white tenure-track faculty suggest that diversity remains a concern in post-secondary music programs.